PENIGKATAN HASIL BELAJAR IPA MENGGUNAKAN MODEL PROBLEM BASED LEARNING BERBANTUAN WORDWALL DI KELAS IV SDN 16 AIR TAWAR TIMUR KOTA PADANG - Anggraini, Rahyu; devi, Masnila; Media, Afriza; Fitria, Yanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low science learning outcomes of fourth-grade students at SDN 16 Air Tawar Timur, Padang City, which were caused by teacher-centered instruction and the limited use of interactive learning media. This study aimed to improve students' science learning outcomes through the Problem Based Learning model assisted by Wordwall. This research employed Classroom Action Research (CAR) using qualitative and quantitative approaches and was conducted in two cycles. Each cycle consisted of four stages: planning, implementation, observation, and reflection. The research subjects were the classroom teacher and 26 fourth-grade students of SDN 16 Air Tawar Timur, Padang City. The research instruments included observation sheets, tests, and non-test instruments. The results showed that the lesson plan assessment increased from 80.36% to 96.43%. Teacher activity improved from 82.14% to 96.43%, while student activity increased from 80.36% to 96.43%. The average student learning outcomes improved from 56.11 in Cycle I Meeting 1 to 79.50 in Cycle I Meeting 2 and reached 92.75 in Cycle II. Therefore, the implementation of the Problem Based Learning model assisted by Wordwall was able to improve students' science learning outcomes in the fourth grade of SDN 16 Air Tawar Timur, Padang City.